2015
DOI: 10.1371/journal.pone.0133195
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Borrelia burgdorferi Sensu Stricto Population and Its Involvement in Borrelia Pathogenicity: Study on Murine Model with Specific Emphasis on the Skin Interface

Abstract: Lyme disease is a multisystemic disorder caused by B. burgdorferi sl. The molecular basis for specific organ involvement is poorly understood. The skin plays a central role in the development of Lyme disease as the entry site of B. burgdorferi in which specific clones are selected before dissemination. We compared the skin inflammatory response (antimicrobial peptides, cytokines and chemokines) elicited by spirochete populations recovered from patients presenting different clinical manifestations. Remarkably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…While this is a limitation of the current study, the major goal was to assess a correlation between expression of type I IFN-related genes and the potential for dissemination, which requires viable spirochetes; qPCR detects DNA from both live and dead spirochetes [ 37 ]. Moreover, several recent studies have found that spirochete DNA present in infected mouse skin is close to the limit of detection by qPCR prior to 72 or 96 h following inoculation, even when using DNA extracted from a much larger quantity of skin than was collected in this study [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While this is a limitation of the current study, the major goal was to assess a correlation between expression of type I IFN-related genes and the potential for dissemination, which requires viable spirochetes; qPCR detects DNA from both live and dead spirochetes [ 37 ]. Moreover, several recent studies have found that spirochete DNA present in infected mouse skin is close to the limit of detection by qPCR prior to 72 or 96 h following inoculation, even when using DNA extracted from a much larger quantity of skin than was collected in this study [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, mice were infected by needle inoculation. This procedure allows for the standardization of parameters, such as the number of spirochetes in the inoculum and the time of inoculation, and has been routinely employed to investigate the early kinetics of B. burgdorferi infection [ 38 , 39 ]. A limitation of this approach is that it does not fully recapitulate physiological infection by tick bite.…”
Section: Discussionmentioning
confidence: 99%
“…The MOI of 100:1 Borrelia used for fibroblast stimulations in microarray and QRT-PCR analyses was chosen to be representative of the physiologic spirochete load present in the dermis at the inoculation site a few days after transmission, when the inflammatory process is culminating. Indeed, although only a small number of Borrelia are present on tick salivary glands and are then inoculated in the dermis during the feeding process [ 23 , 24 ], an intense replication of Borrelia occurs after inoculation in the host skin at the inoculation site, peaking at day 7 after inoculation [ 25 , 26 ]. Moreover, setting the stimulation conditions at MOI of 100:1 for 24 hours enabled to yield a potent activation of human dermal fibroblasts while allowing the experimental conditions to emulate those of our first study assessing the early transcriptional response (at 24 hours) of human dermal fibroblasts stimulated by three strains of B .…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates previous studies reporting the induction of CXCL1, IL6 and IL8 in Borrelia -stimulated primary human fibroblasts in vitro [ 19 , 34 ]. Borrelia -induced stimulation of dendritic cells and macrophage chemoattractants was also demonstrated in skin biopsies of murine models (MCP-1, also referred to as CCL2) [ 26 ], as well as in human biopsies of EM and ACA lesions (CCL2, CXCL1, CXCL9, CXCL10, and CCL20) [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, this relationship has been shown in rodent malaria where the parasite density in the blood is critical for mouse-to-mosquito transmission (59). For B. burgdorferi sl pathogens, the skin rather than the blood is the critical tissue for host-to-tick transmission (60, 61). Field studies on B. afzelii in bank voles and other wild rodents found a positive relationship between the spirochete load in the ear tissues and transmission to larval I. ricinus ticks (62).…”
Section: Discussionmentioning
confidence: 99%